ENTERPRISE ARCHITECTURE DESIGN USING TOGAF ADM IN BUDGET PLANNING AND CONTROLLING FUNCTIONS (CASE STUDY: TELKOM CORPORATE UNIVERSITY CENTER) - Muhammad Ahdani Himam Himam Mutaali (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The development of information systems and information technology is very important because it has an impact on increasing interaction resources for all fields, thus helping to realize the company's goals. But not all companies can implement and develop appropriate information system technology to meet their needs and get solutions to their problems, including the Telkom Corporate University Center (TCUC). TCUC is part of PT Telekomunikasi Indonesia, which is engaged in accelerating the science and technology-based transformation process and developing digital talent capabilities. TCUC has several units, one of which is the Planning and Controlling unit in which there is a Budget Planning and Controlling function. In connection with advances in information technology, especially in the Budget Planning and Controlling function, there are several obstacles. Exchange of data related to the provision of a budget that is not yet optimal, causes discrepancies in the realization of the budget for other units. Therefore, an Enterprise Architecture (EA) solution is needed to align business and technology needs. Enterprise Architecture (EA) is designed using the TOGAF ADM method. EA design starts from the preliminary phase to the technology architecture. The result of this research is an Enterprise Architecture Blueprint which is expected to be able to solve the problems experienced and become a project proposal guide to assist the implementation and development of the right information technology system for the Budget Planning and Controlling function.